Effects of Active Hexose Correlated Compound (AHCC®) on Clinical and Laboratory Response of Pulmonary Tuberculosis Patients - Madolangan, Jamaluddin; Yusuf, Irawan; Wahyudin, Elly; Djaharuddin, Irawaty (Jurnal Respirologi Indonesia, 2025)
Backgrounds: Active hexose correlated compound (AHCC), an α-glucan extracted from Lentinula edodes, is known for its immunomodulatory properties. It is suspected that the strong nutrients contained in AHCC are very safe and without side effects, including in tuberculosis patients. This study evaluated the effect of AHCC on clinical and hematologic responses in pulmonary tuberculosis (TB) patients Methods: A double-blind randomized controlled trial was conducted involving 60 pulmonary TB patients receiving standard anti-TB therapy. Participants were randomly assigned to receive either AHCC (3 g/day) or a placebo for six months. Clinical and laboratory parameters were assessed before and after treatment. Results: Patients in the AHCC group showed greater improvement in clinical symptoms (reduced cough, improved appetite, and weight gain) and significant enhancement of hematological and immunological markers compared with placebo (P<0.05). AHCC supplementation significantly increased CD4⁺ and CD8⁺ lymphocyte counts, suggesting improved immune recovery and modulation of host defense against Mycobacterium tuberculosis infection. Conclusion: AHCC supplementation alongside standard anti-TB therapy improves clinical outcomes and immune responses in patients with pulmonary tuberculosis.